Inclusão molecular da oleuropeína e do Butil Hidroxianisol (BHA) em alfa e beta-ciclodextrina - Barão, Carlos Eduardo (2008)
The objective of this work was to promote the inclusion of two antioxidants, the BHA (butylated hydroxyanisole, artificial antioxidant very used in oils) and the oleuropein (natural antioxidant extracted of olive leaves tree), with a-cyclodextrin (a-CD) and ß-cyclodextrin (ß-CD) and make the characterization of those complex, through the calculation of the complexation constant and thermal analyses of TGA and DSC. In the first stage, were they made the procedures for obtaining the constant of complexation between methylorange (MO) and cyclodextrins (a- CD and ß- CD), those data would be used in the determination of the constant between oleuropein and the cyclodextrins. For complexation between the dye and CDs were verified that the best pH to work was 3.0; being used citrate/sodium phosphate dibasic buffer, in the wavelength of 500nm and being used as maximum concentration 0.045 x 10-3 mol L-1 of dye in the solutions. The complexation constants obtained in those cases went 4557.2 M-1 for the compound formed between a- CD and MO, and 952.00 M-1 to the complex formed with ß-CD:MO. In both cases it was verified that the molar absorptivity of the compounds decreased, almost third, after the complexation with cyclodextrins. In the second stage, it was obtained the wavelength of maximum absorption of the aqueous solution of pure oleuropein and complexed with ß-CD, being verified the absorbance of oleuropein does not change when complexed with this cyclodextrin. After that, being used the data obtained in the procedure of complexation of methylorange with the cyclodextrins as parameter, it were determined the constants of complexation between oleuropein and cyclodextrins. For the compounds done form among a-CD:oleuropein and ß-CD:oleuropein, it was obtained the values of 1352.4 M-1 and 1827.9 M-1 respectively. In the third stage, were accomplished the studies involving BHA with both cyclodextrins. Initially it was obtained an equation that relates the concentration of the aqueous solution of BHA with its respective absorbance and its solubility in water, that was 0.1415 g L-1. The tests to verify if the cyclodextrins influence in the spectrum of sweeping of the solutions of BHA with the time, showed that did not happen changes in the course of time in the absorption of the solution of BHA. Through the phase solubility studies, were obtained the values of the constant of complexation between BHA and cyclodextrins, resulting in 49.31 M-1 and 585.3 M-1 for the compounds form among the a-CD and the ß-CD respectively, with an increase of 621% and of 126% on the solubility of BHA in water, when are they in the presence of the a- CD and the ß-CD, respectively. On the last stage the inclusion complex were prepared by kneading and physical mixtures following for the characterization tests of the compounds were accomplished for Thermogravimetric Analyses (TGA) and Differential Scanning Calorimetry (DSC). The a-CD: oleuropein interaction, the peaks of melting and boiling point, corresponding to the compounds did appear with little late, when compared with the pure substances, indicating partial formation of the complex. In the physical mixtures the peaks appeared more accentuated, but again the interpretation was hindered, because it happened the same behavior of a- CD. To DSC of BHA and a- CD, it can be verified that there was not interaction of any type between the compositions. The interactions between oleuropein and ß- CD, can be confirmed the formation of complex in the 1:2 preparation, and in the other cases, happened weak interactions. The thermograms of the inclusion complex involving BHA and the ß- CD (in 1:1 preparation as much as in the 1:2 preparation), it was observed the disappearance of the melting peak of pure BHA, while for the thermograms of physical mixtures, this peak appears very defined (mainly in the preparation 1:1). For the tests of thermogravimetric analyses involving a- CD, or ß- CD, with oleuropein, the volatilização of this last one compound seems to have happened in a slower way indicating the complex formation. In the case between BHA and a-CD, it showed little or any interaction between both. But for BHA and ß-CD verified the complex inclusion do not present the volatization stage of free BHA (more visible in the 1:1 complex), demonstrating the formation of the complex inclusion.